Association of ADIPOQ, leptin, LEPR, and resistin polymorphisms with obesity parameters in Hammam Sousse Sahloul Heart Study. Issue 6 (13th February 2017) - Zayani, Nesrine; Omezzine, Asma; Boumaiza, Imen; Achour, Ons; Rebhi, Lamia; Rejeb, Jihen; Ben Rejeb, Nabila; Ben Abdelaziz, Ahmed; Bouslama, Ali
Abstract : Background: Adipose tissue is an important endocrine organ that secretes a number of adipokines, such as adiponectin (ADIPOQ), leptin (LEP), leptin receptor (LEPR), and resistin (RETN) which may be implicated in obesity. Some adipokines' polymorphisms of genes might influence their concentrations and/or activities. Our aim was to study the relationship between seven SNPs in ADIPOQ (+45T<G (rs2241766); +276G<T (rs1501299); −4255C<T (rs822393); −395G<T (rs17366568)), LEP (2548G<A (rs7799039)), LEPR (223Q<R (rs1137101)), and RETN (‐420C<G (rs1862513)) and obesity in Hammam Sousse Sahloul Heart Study (HSHS). Methods: The study, carried out between February and June 2009, is mainly focused on 1121 respondents in HSHS which is a population‐based epidemiological study of type "community‐based" on cardiovascular risk. Genotyping was performed using polymerase chain reaction–restriction fragment length polymorphism (PCR‐RFLP). Serum lipids and anthropometric parameters were measured. Statistic analysis was performed on SPSSv19. Results: The polymorphisms of ADIPOQ 4522C<T and 276G<T, LEP 2548G<A, and RETN 420C<G seem to contribute to obesity. In fact, adjusted odds ratios (ORs) of obesity associated with mutated genotypes of each polymorphism were respectively OR=1.38, P =.037; OR=0.608, P <.001; OR=2.23, P =.034; and OR=2.18, P <.001. The 276G<T, 4522C<T, and 420C<G were associated with increased BMI ( P =.010, P =.028, and P <.001). A significant association was found between the 276G<T; 4522C<T, LEP 2548G<A and 420C<G, and the waist circumference and hip measurements. Conclusion: ADIPOQ, LEP, and RETN gene polymorphisms were associated with obesity parameters in HSHS population.